Obra lírica de Leandro Fernández de Moratín: versos entre el Neoclasicismo y la Ilustración - Palacios Fernández, Emilio (Cuadernos de Historia Moderna, 2008)
The poetical works of Leandro Fernandez de Moratín were written during the last two decades of the eighteenth century and early in the next century; however they were not fully known until the publication of the book titled Obras dramáticas y líricas (1825). He was most famous as a neoclassical and enlightened playwright who as a poet of the Second Neoclassical Generation. Moratín joined the old and universal topics of Horace but also showed his enlightened ideas on ethics, politics, religion, society, economy and trade, justice, the new literature, and the merits of the Bourbon Monarchy.